Pengaruh Metode Quantum Ikhlas Terhadap Perubahan Kadar Imunoglobulin G Pada Ibu Nifas - Sri Rahayu; Sri Wahyuni; Runjati Runjati (Politeknik Kesehatan Kementrian Kesehatan Semarang, 2023)
The prevalence of low birth weight babies (LBW) is around 6.2% and they die during the neonatal period. Separated baby care affects the psychology of postpartum mothers and negative coping mechanisms. The purpose of this study was to prove the effect of giving the Quantum Ikhlas Method (MQI) on IgG levels in postpartum women. Types of research design was Quasi experimental Research, Pretest and posttest with control group design. The population was all postpartum women who gave birth to LBW at Tugurejo Semarang Hospital and Semarang City Hospital from August to October 2019. The total sample was 25 divided into 2 groups, taken stratified random sampling. Methods of data collection for group I MQI treatment and group 2 control according to hospital standards. The research was held after obtained the consent of the respondent, a pretest was to measure the level of IgG in the treatment and control groups, the treatment was carried out 3 times in two weeks postpartum and posttest. Data was analyzed with test-dependent and independent tests. The results showed that the average age of the respondents was in the range of 22.5 years to 23.9 years. The education in the treatment and control groups was secondary. 7 increased to 5.9 mg/ml, and the control group averaged 6.07 mg/ml decreased to 5.28 mg/ml. Conclusion of the study was there was an effect of MQI on changes in Ig G. All postpartum mothers can increase their gratitude and acceptance for the conditions of their baby's birth by applying MQI.